2023
DOI: 10.1055/s-0043-1771470
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Dysfunction in Stroke

Abstract: Gastrointestinal (GI) complications are seen in over 50% of ischemic stroke survivors; the most common complications are dysphagia, constipation, and GI bleeding. The bidirectional relationship of the gut–brain axis and stroke has recently gained traction, wherein stroke contributes to gut dysbiosis (alterations in the normal host intestinal microbiome) and gut dysbiosis perpetuates poor functional neurologic outcomes in stroke. It is postulated that the propagation of proinflammatory cells and gut metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 206 publications
(401 reference statements)
0
3
0
Order By: Relevance
“…First, dysphagia after IS decreased esophageal sphincter muscle tone, and impairment of normal gastrointestinal motility function are important risk factors leading to the occurrence and aggravation of GERD. In addition, stroke can also exacerbate gastrointestinal symptoms such as dysphagia by affecting nutritional factors and neural centers regulating intestinal motility and appetite, such as the sympathetic and parasympathetic medulla and hypothalamic center, thereby further increasing the risk of GERD ( 4 ). Second, recent studies have found that the normal microbiota of the intestinal mucosa of mice is destroyed after brain injury caused by stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, dysphagia after IS decreased esophageal sphincter muscle tone, and impairment of normal gastrointestinal motility function are important risk factors leading to the occurrence and aggravation of GERD. In addition, stroke can also exacerbate gastrointestinal symptoms such as dysphagia by affecting nutritional factors and neural centers regulating intestinal motility and appetite, such as the sympathetic and parasympathetic medulla and hypothalamic center, thereby further increasing the risk of GERD ( 4 ). Second, recent studies have found that the normal microbiota of the intestinal mucosa of mice is destroyed after brain injury caused by stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Some past studies have found that nearly 50% of stroke patients will develop gastrointestinal complications such as dysphagia and gastrointestinal bleeding after the disease ( 4 ). In addition, because of the close connection between the esophagus and the left atrium, GERD is thought to have an intimate role in atrial fibrillation, and some studies have linked GERD to an increased risk of atrial fibrillation, which increases the risk of stroke ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has established a significant association between stroke and malnutrition ( 9 ). Specifically, stroke substantially increases feelings of fatigue, impairs digestive function, and leads to negative psychological states, ultimately resulting in individual malnutrition ( 10 , 11 ). Moreover, dysphagia in Stroke Patients with Bulbar Paralysis (SPBP) is typically severe ( 12 ).…”
Section: Introductionmentioning
confidence: 99%